IT and administrative culture in India - Mukhopadhyay, Asok (2000)
The author briefly analyses the changes and breakthroughs brought about by fast developing IT from typewriter age to Internet, EDI and CD. He then examines impact of these technological developments on the administrative culture affecting both structure and nature of administrative functions, and management patterns as reflected from the need to devise strategic information system or information superhighway, free and easy access to cyber space, and emphasis on team spirit, transparency and free flow of information for good governance. - Reproduced
Keywords: E governance - India; Public administration - India; Information technology - India; Information technology